2005
DOI: 10.1096/fj.04-3664fje
|View full text |Cite
|
Sign up to set email alerts
|

Novel drug development opportunity for relaxin in acute myocardial infarction: evidences from a swine model

Abstract: The hormone relaxin has been shown to cause coronary vasodilation and to prevent ischemia/reperfusion-induced cardiac injury in rodents. This study provides evidence that relaxin, used as an adjunctive drug to coronary reperfusion, reduces the functional, biochemical, and histopathological signs of myocardial injury in an in vivo swine model of heart ischemia/reperfusion, currently used to test cardiotropic drugs for myocardial infarction. Human recombinant relaxin, given at reperfusion at doses of 1.25, 2.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 35 publications
8
82
0
1
Order By: Relevance
“…21 The anti-apoptotic effects of relaxin in the infarcted murine heart are also consistent with its effects in a porcine model of MI, 36 and its ability to protect cardiomyocytes from apoptosis in vitro; 16 while its pro-angiogenic Relaxin remodels post-infarct fibrotic healing CS Samuel et al effects are in keeping with that observed in the pig model of MI. 14 The rationale for Glut-1 staining was based on previous studies using endothelial expression of Glut-1 as a marker of active de novo capillary formation; where 75% of Glut-1 expression in the heart was localized to the capillary endothelium.…”
Section: Discussionsupporting
confidence: 56%
“…21 The anti-apoptotic effects of relaxin in the infarcted murine heart are also consistent with its effects in a porcine model of MI, 36 and its ability to protect cardiomyocytes from apoptosis in vitro; 16 while its pro-angiogenic Relaxin remodels post-infarct fibrotic healing CS Samuel et al effects are in keeping with that observed in the pig model of MI. 14 The rationale for Glut-1 staining was based on previous studies using endothelial expression of Glut-1 as a marker of active de novo capillary formation; where 75% of Glut-1 expression in the heart was localized to the capillary endothelium.…”
Section: Discussionsupporting
confidence: 56%
“…The inhibition of either the nitric oxide pathway or glucocorticoid receptor stimulation significantly reduced the positive effects described previously for homogenous groups (10)(11)(12). Surprisingly for group 7 when we associated both inhibitors the severity that was developed although greater than for homogenous groups (6-7) was still less than that displayed by homogenous groups (3)(4) suggesting that there is another pathway involved in the treatment with relaxin.…”
Section: Pancreatic Edemamentioning
confidence: 55%
“…It has been reported that relaxin offers protection for reperfusion-induced cardiac injury increasing coronary blood flow favoring blood supply to the ischemic myocardium while it exerts a relaxant action on smooth muscle cells [10] . It has been shown that relaxin up regulates nitric oxide synthase (NOS) II expression thus inducing nitric oxide mediated vasodilatation by a controlled activation of endogenous nitric oxide biosynthesis [11] .…”
Section: R E L a X I N P R E V E N T S T H E D E V E L O P M E N T O mentioning
confidence: 99%
See 1 more Smart Citation
“…This working hypothesis is based on the following mainstays: ( i ) blood vessels are a physiological target of RLX and their cells express the specific RLX receptor RXFP1 25; ( ii ) RLX up‐regulates NOS expression and nitric oxide production in vascular endothelial cells 26, 27, 28, 29, 30; ( iii ) RLX improves inflammation‐induced endothelial dysfunction and NOS fall 31, 32; and ( iv ) RLX reduces oxidative stress and nitric oxide failure in different animal models of vascular injury 33, 34, 35, 36, 37.…”
Section: Introductionmentioning
confidence: 99%